Logistics Management in Maritime Transportation Systems - M. Coccola; C.A. Mendez (Chemical Engineering Transactions, 2013)
The efficient routing and scheduling of multi-parcel chemical tankers is a challenging problem for both chemical and shipping industry. To optimally manage complex logistics problem, a novel continuous time precedence-based MILP mathematical formulation is developed to determine the optimal solution to the ship routing and scheduling. The approach aims to determine the assignment of cargos to ships and define the optimal route that each ship should follow to maximize its profit. The MILP-based model is then combined with an iterative algorithm in order to tackle large-scale problems involving a large numbers of ships, ports, and cargos. To illustrate the applicability and importance of the proposed method, a real industrial case study taken from literature is solved with modest CPU times.